ANTESEDEN DARI BEHAVIOURAL INTENTIONS PADA JAJANAN KAKI LIMA DI JAKARTA - Sabilla, Dinda Syahbani; Kurniawati, Kurniawati (STKIP Persada Khatulistiwa Sintang, 2024)
The problem in this study is that food safety is the main issue, there are also other issues such as poor sanitation, traffic congestion, and social issues such as child labour, street food poses a risk of poisoning because sellers often do not understand the causes of food-borne diseases although customers pay attention to hygiene, they are often unaware of the health risks of street food. The objectives of this study include to determine the effect of service quality, physical environment, perceived value, customer satisfaction, and behavioural intention. Data was obtained through the method of distributing questionnaires to 250 respondents in Jakarta, who like to buy street food in the area of gondangdia station, cikini station, Tangerang old market, block M. Data used such as cross-sectional data and applying purposive sampling into the sampling method. Analytical tools used such as structural equational modelling (SEM). The results of hypothesis testing explain if service quality has an impact on customer satisfaction, the physical environment has a good impact on customer satisfaction, perceived value has a good impact on customer satisfaction, and customer satisfaction has a good impact on behavioural intentions. This study obtained implications for street food sellers in the four areas to strengthen the quality of their food and also the cleanliness of the selling area, then street food sellers must pay attention to variables such as service quality, physical environment, perceived value, customer satisfaction, and behavioural intentions.